Gerakan Transnasional Kristen: Wajah Ekonomi-Politik Agama dan Pendidikan di Indonesia - Elia Tambunan (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2019)
Although a number of prominent Church declared the Western imperialism and colonialism is not at all played an important role in the diffusion of the Christian religion and education in Indonesia, this paper, with a historical approach, read resource Indonesianis, Church, Islam, interviews and explanations of Christian figures competent in certain meetings, finds other things. The Christianization of Indonesia conducted through education is the historical fact of transnational movement of Christianity in Indonesia. The movement was a religious and educational shows by State actors and non-State since the days of colonialism and imperialism of Western mutual intertwinly. It's never